2009
DOI: 10.3945/jn.108.099259
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Aryl Hydrocarbon Receptor-Mediated Activation of Cyclooxygenase-2 Expression by the Indole-3-Carbinol Metabolite 3,3′-Diindolylmethane in Breast Cancer Cells

Abstract: Ligands of the aryl hydrocarbon receptor (AhR) include the environmental xenobiotic 2,3,7,8 tetrachlorodibenzo(p)dioxin (TCDD), polycyclic aryl hydrocarbons, and the dietary compounds 3, 3'-diindolylmethane (DIM), a condensation product of indol-3-carbinol found in Brassica vegetables, and the phytoalexin resveratrol (RES). The AhR and its cofactors regulate the expression of target genes at pentameric (GCGTG) xenobiotic responsive elements (XRE). Because the activation of cyclooxygenase-2 (COX-2) expression b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 33 publications
3
62
0
Order By: Relevance
“…DIM appears to elicit multiple targets anticancer effects through many potential mechanisms including antiinflammation, antioxidative stress effect, cell-cycle regulation, and apoptosis depending on the context of tissues and cell types (10,(34)(35)(36)(37)(38). Several naturally occurring anticancer phytochemicals have been shown to possess the ability to prevent cancer via epigenetic modifications (14,15,(39)(40)(41). A previous study showed that DIM possesses the ability to inhibit HDAC activity which correlated with increased expression of p21in both human PC-3 and LNCaP cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…DIM appears to elicit multiple targets anticancer effects through many potential mechanisms including antiinflammation, antioxidative stress effect, cell-cycle regulation, and apoptosis depending on the context of tissues and cell types (10,(34)(35)(36)(37)(38). Several naturally occurring anticancer phytochemicals have been shown to possess the ability to prevent cancer via epigenetic modifications (14,15,(39)(40)(41). A previous study showed that DIM possesses the ability to inhibit HDAC activity which correlated with increased expression of p21in both human PC-3 and LNCaP cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…35 Evidence from mammary cell lines has demonstrated the role of DIM in reducing oxidative stress by stimulating the phosphorylation of BRCA1. 36 Further, DIM has a demonstrated role in reducing cyclooxygenase-2-induced inflammation in mammary cell lines.…”
Section: Promotion Of Breast Tumorsmentioning
confidence: 99%
“…36 Further, DIM has a demonstrated role in reducing cyclooxygenase-2-induced inflammation in mammary cell lines. 35 In advanced stages of tumor development, DIM has been shown in tumor cell line models to inhibit the expression of genes involved in angiogenesis and energy metabolism, including those involved in the induction of survivin 37 and hypoxiainducible factor-1. 38 The interferon-c signaling pathway also is activated by DIM through the interferon-c receptor and the interferon-c-responsive proteins p56-and p69-oligoadenylate synthase, which inhibit growth of human breast cancer cells, resulting in inhibition of cell proliferation.…”
Section: Promotion Of Breast Tumorsmentioning
confidence: 99%
“…Such compounds include low-molecular-weight aliphatic isothiocyanates, 13 phenethyl isothiocyanate, 14,15 and two products of indole glucosinolate degradation, indole-3-carbinol and diindolylmethane. 16,17 In contrast to these beneficial effects of glucosinolates, there is evidence (primarily from animal studies) of adverse effects on the thyroid caused by the glucosinolate progoitrin, from which the product of myrosinase-induced degradation is goitrin (Figure 1). [18][19][20][21] Iodine is a dietary micronutrient required for the production of thyroid hormone, and the potential adverse effects of goitrin and thiocyanates are based on their ability to inhibit iodine utilization by the thyroid.…”
Section: Introductionmentioning
confidence: 99%